2017
DOI: 10.1148/radiol.2016160355
|View full text |Cite
|
Sign up to set email alerts
|

Self-gated Non–Contrast-enhanced Functional Lung MR Imaging for Quantitative Ventilation Assessment in Patients with Cystic Fibrosis

Abstract: Purpose To assess the clinical feasibility of self-gated non-contrast-enhanced functional lung (SENCEFUL) magnetic resonance (MR) imaging for quantitative ventilation (QV) imaging in patients with cystic fibrosis (CF). Materials and Methods Twenty patients with CF and 20 matched healthy volunteers underwent functional 1.5-T lung MR imaging with the SENCEFUL imaging approach, in which a two-dimensional fast low-angle shot sequence is used with quasi-random sampling. The lungs were manually segmented on the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 23 publications
4
53
0
Order By: Relevance
“…10,20,27 In the present study we also showed significant correlations of FD-FV with clinical lung function test parameters such as FEV1. 15 A limitation of this study was the fact that no chest CT data were available in this cohort. While pulmonary function testing is still the clinical gold standard for grading COPD severity and treatment recommendations, assessment of regional lung ventilation may play an import role in phenotyping of COPD patients in the future.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…10,20,27 In the present study we also showed significant correlations of FD-FV with clinical lung function test parameters such as FEV1. 15 A limitation of this study was the fact that no chest CT data were available in this cohort. While pulmonary function testing is still the clinical gold standard for grading COPD severity and treatment recommendations, assessment of regional lung ventilation may play an import role in phenotyping of COPD patients in the future.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15] FD-MRI is radiation-and contrast-agent free, cost-efficient, and patient-friendly, but has yet not been validated in COPD patients for its potential properties to measure regional lung ventilation. [13][14][15] FD-MRI is radiation-and contrast-agent free, cost-efficient, and patient-friendly, but has yet not been validated in COPD patients for its potential properties to measure regional lung ventilation.…”
mentioning
confidence: 99%
“…The mean QV values of the group of healthy subjects were compared between UTE‐SENCEFUL (with the 3D image registration) and 2D‐SENCEFUL using a 2‐tailed Mann Whitney test. The regional QV was also evaluated for the patient and compared to a previous study …”
Section: Methodsmentioning
confidence: 99%
“…The latter is used to separate the acquired data into individual respiratory and cardiac phases, ultimately yielding representative respiratory and cardiac cycles. After image registration, the signal amplitude of the first harmonic in the frequency domain is selected to depict the functional contrast in the lung …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation